The Influence of Location Determination, Price, and Product Quality on Consumers' Purchase Interest in Thrift Clothing in Malang City - Maria Cerciayati Lisim; Cakti Indra Gunawan; Imam Hidayat (IRDH International Journal of Social Sciences & Humanities, 2026)
This study aims to analyze the influence of location, price, and product quality on consumers' purchasing interest in thrifting clothing in Malang City. The research sample consisted of 200 respondents who are active thrift shop consumers, selected using purposive sampling techniques. Data were collected through a questionnaire with a 1–5 Likert scale and analyzed using multiple linear regression. The results of the study indicate that, partially, the variables of location, price, and product quality have a positive and significant effect on consumers' purchasing interest. Product quality is the most dominant variable in influencing purchasing interest. In addition, the simultaneous test (F-test) shows that these three independent variables together have a significant effect on purchasing interest. The practical implications of this study emphasize the importance for thrift shop managers to consider strategic location, competitive pricing, and maintain product quality in order to increase consumer purchasing interest. This research is expected to serve as a reference for the development of marketing strategies in the thrifting industry in Malang City.